The improvisers - Glover, Nicole (Glover, Nicole. Murder & magic, 2024)
Velma Frye is many things. A pilot, a former bootlegger, a well-seasoned traveler, a jazz pianist...and a wielder of celestial magic. She's also a member of the mystical Rhodes family as well as an investigator for arcane oddities for a magic rights organization, dealing with both simple and complicated cases. And when a pocket watch instigates a magical brawl after one of her flight shows, things become very complicated.